Kinetic Study of Removal of Congo Red and Direct Green. Issue 1 (August 2021) - Said, Muhammad; Indwi Saputri, Lavini; Hasanudin,; Loekitowati Hariani, Poedji; Yong, Ng Law
Abstract: The pillarization process of Al/Fe metal oxide compound in bentonite has been carried. The study of weight adsorbent, pH, adsorption time, concentration and temperature adsorption were investigated to get the optimum condition of Congo red and Direct green removal. In addition, the pseudo kinetic and isotherm model were also determined to investigate the rate and type of adsorption. From the experiment, the optimum weight of adsorbent, pH, adsorption time, concentration and temperature were 0.3 g, 2, 45 minute, 90 mg/L, respectively. Thus, the pseudo kinetic model follow the pseudo second order while the Freundlich model was use as the isotherm model. As conclusion, The Pillarization success to enhance the adsorption capacity of bentonite to remove the Congo red and Direct green dyes.